The Relation Between the Nutrition Status and Mobilization Through the Length of Stay Post Appendictomy at An-Nisa and Gambiran Hospital - Suci Nurjanah (Universitas Muhammadiyah Ponorogo, 2019)
the management of appendicitis in chilidren is appendictomy with the laparatomy method by tapping or saving the appendix using an icision under the rigth abdomen. The causes factor to the healing process of wound after surgency which influence the leggth of stay among others, children’s nutrition satatus and mobilization. The purpuse of thr study was to know the relation between the nutrition status and mobilization through the length of stay post appendictomy at An-Nisa and Gambiran Hospital. The reseach desaign was analytic observation with cross sectional apporch. The number of sampel is 34 respondent which is determined by total sampling method. Data were analyzed by univriat and bivariat. The value nutriton status 0,001and mobilization 0,030 with the length of stay for childreen post appendictomy. Based on the result, it is recommended that nurse provide health education related the improtance of mainting wegth and mobilzation to the children post appendictomy so the legth of stay doesn’t take too long